Linguistic purism in the Germanic languages - Langer, Nils; Davies, Winifred V. (Studia linguistica Germanica, 2005)
This volume deals with linguistic purismin itsmany realizations.In particular, the articles look at the relationship of purism to historical prescriptivism (e.g. the influence of grammarians in the 17th and18th centuries), to nationhood (e.g. the instrumentalising of purism in the standardisation of Afrikaans or Luxembourgish), to modern society (e.g. the existence of puristic tendencies in computer chatrooms), to folk linguistics (e.g. lay perceptions of different varieties of English), and to academic linguistics (e.g. the presence of puristic notions in the historiography of German or English)
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Konferenzschrift -- Bristol >2003>; Konferenzschrift -- 2003 -- Bristol; Sprachpurismus; Germanische Sprachen